Environmental perspectives for food loss reduction via smart sensors: A global life cycle assessment. (10th November 2022) - Zhu, Jingyu; Luo, Zhenyi; Liu, Yuru; Tong, Huanhuan; Yin, Ke
Abstract: This study incorporates theoretical and empirical perspectives in developing an understanding that, whether there is a leverage on the key environmental impacts through the potential large-scale application of Internet of Things (IoT) in the food supply chain, assisted with integrated shelf life-food loss and life cycle assessment (SL-FL-LCA) model. Environmental cost of IoT sensors and benefit from food loss (FL) reduction were both accounted. Sensor manufacturing, led by precious metals consumption, shows strong multiple toxicological effects, underscoring the importance of proper E-waste management and adoption of environmentally friendly materials. Avoiding FL (which will reserve 20–41% of the FL of perishable foods) and subsequent avoidance in the FL treatment further promoted the net gains, while brought multiple benefits in aspects of abiotic depletion (Sb), terrestrial ecotoxicity, photochemical oxidation, acidification, and eutrophication. Partially negative results on abiotic depletion (fossil fuels), ozone layer depletion, human toxicity, freshwater, and marine aquatic ecotoxicity were noted though, advancements in targeted sensor materials and technology innovation could eliminate these shortcomings. With current sensor technology, the optimal deployment of IoT sensors dependent on various food types and regions, suggesting the combination of multiple factors to sustain the IoT application, which are essential to reconcile competing objectives. Highlights: Component of sensor module for meat products brings the worst impact. Metals recovery in E-waste treatment offsets most adverse effects in manufacturing. Highest benefits occur in sensors application for fruits and vegetables. Sensors application indicates leverage effect on 7 environment aspects in 10 indexes.